Muʻjam al-shuʻarāʼ : min al-ʻAṣr al-Jāhilī ḥattá sanat 2002 M - Jubūrī, Kāmil Salmān. (Bayrūt : Dār al-Kutub al-ʻIlmīyah, 2003)
Poets, Arab; biography; dictionaries.
Includes bibliographical references (v. 6, p. 369-477).
Keywords: Poets, Arab -- Biography -- Dictionaries; Poets, Arab; Biography -- Dictionaries